Efficacy of biological treatment in inflammatory bowel disease – a single-center experience - Michalak, Agata; Kasztelan-Szczerbinska, Beata; Laskowska, Katarzyna; Radwan, Piotr; Cybulski, Marek; Cichoż-Lach, Halina (Polish Journal of Public Health, 2020)
Introduction. Efficacy of biological treatment (BT) is a key issue among inflammatory bowel disease (IBD) patients. Laboratory markers and endoscopic procedures are basic diagnostic tools in the assessment of response to biological agents in the course of Crohn’s disease (CD) and ulcerative colitis (UC). Aim. The aim of our investigation was to assess the correlation between laboratory parameters and endoscopic picture in the course of BT in patients with IBD – CD and UC –treated with biological agents. Material and methods. The total number of 71 patients were enrolled in the study, 25 with CD and 46 with UC. When it comes to 15 patients with CD, they were treated with infliximab (IFX) and 10 patients with adalimumab (ADA) – one year of therapy. Patients with UC were administered IFX – induction therapy. Laboratory tests (C-reactive protein (CRP) and platelet (PLT) count) and colonoscopy were performed in all patients before and during BT. Results. BT improved endoscopic picture (SES-CD, MAYO) in all patients. BT lowered CRP (p